An oil-source rock correlation examining the potential of the Chattanooga shale as a source rock for oil within the Spivey-Grabs-Basil Field, Kingman and Harper Counties, Kansas - Wall, Meagan (Kansas State University, 2015)
Oil production in Kansas has a long history with plays being found on all sides of the state. The source of Kansas’s hydrocarbons has been traditionally thought to be outside the state due to low thermal maturity and the shallow burial of potential source rocks within Kansas. This research addresses the question regarding the source of the oil in Kansas, at least within a small geographic area of roughly 146mi[superscript]2. The Spivey-Grabs-Basil Field has been one of the more successful fields within the state of Kansas since the 1960’s. This field is compartmentalized and offers a natural laboratory in which to conduct the field’s first formal oil-source rock correlation since oils are locked into place. While the main focus of this research relies heavily on pyrolysis and GCMS for biomarker analysis, it also investigates the possibility of using rare earth element (REE) concentrations as a possible fingerprint of organic matter within a source bed. TOC values of the Chattanooga shale samples from the Spivey-Grabs-Basil filed range from 0.75 and 3.95 wt. %, well within productive capacity. Pyrograms show both the potential for additional production, and the likely previous expulsion of hydrocarbons. Biomarker concentration percentages between C[subscript]27, C[subscript]28, and C[subscript]29 steranes, as well as pentacyclic terpane ratios compared between crude oil from the Spivey-Grabs-Basil and the Chattanooga shale show a definite genetic relationship. REE values of the organic fraction of the Chattanooga inversely correlate with those of the crude oils, suggesting fractionation during oil generation. After comparison of results with the Woodford shale in Oklahoma, the conclusion of this study is that the Chattanooga shale which underlies the Spivey-Grabs-Basil oil field of southern Kansas is the probable source rock which generated the oil now being produced.
Keywords: Biomarkers; Correlation; Spivey-Grabs-Basil; Rare Earth Elements; Chattanooga shale; Woodford shale; Geochemistry (0996); Geology (0372); Petroleum Geology (0583)